A primary investigation of the relation between the incidence of brucellosis and climatic factors in Iran. (February 2020) - Dadar, Maryam; Shahali, Youcef; Fakhri, Yadolah
Abstract: Brucella spp. are Gram-negative coccobacilli that may grow in different media and environmental conditions for extended periods of time. The survivals of these bacteria in the environment have an important impact on the epidemiology of brucellosis worldwide. The effect of climate on the incidence of certain zoonotic infectious diseases, (recently referred to as climate-sensitive zoonosis) is now well established. The aim of this study was to evaluate the relation between the incidence of brucellosis and climatic parameters in Iran, an important endemic region for brucellosis with diverse climate. The information on the incidence of human brucellosis in different Iranian provinces for 2016 has been provided by the Ministry of Health and Medical Education, Iran. Annual meteorological data collected between 2015 and 2016 were obtained from the Iranian Meteorological organization (IMO). A regression analysis of the incidence of brucellosis was performed via STATA 14.0 and the heterogeneity among observations was determined via Cochrane's Q-test and I 2 statistic. If I 2 index was higher than 50%, heterogeneity was considered as considerable. The results of regression analyses revealed a negative significant association between mean ambient air temperature and brucellosis incidence (C = - 0.022, P value = 0.004). Likewise, a positive significant association was found between number of frosty days and brucellosis incidence (C = 0.002, p value = 0.003). Other metrological parameters showed no significant effect on the human brucellosis incidence. Although our results suggest a high degree of temperature sensitivity in regards to the brucellosis incidence in Iran, this study opens up prospects for further investigations regarding environmental conditions and climatic changes influencing the spatial distributions and seasonal/annual cycle of this zoonotic pathogen worldwide. Highlights: In most parts of Iran the annual incidence of human brucellosis remains high. A negative significant association exists between mean ambient air temperature and brucellosis incidence. The incidence of the disease showed decreasing tendency when mean temperatures exceed 19 °C. A positive significant association exists between number of frosty days and brucellosis incidence. The hot coastal dry climate with average maximum temperature exceeding 30 °C showed the lowest incidence.